Differences in close-work activities and optical axis length between only children and non-only children: a cross-sectional study - Yanhui Wang; Yaoyao Lin; Dandan Jiang; Linjie Liu; Shudan Lin; Juan He; Youping Liang; Bing Sun; Yanyan Chen (BMC, 2022)
Abstract Background This study aimed to investigate the differences in optical axial length and close-work activities between only children and children with siblings in Wenzhou. Methods This was a cross-sectional population-based study. In total, 2913 school-aged children and their parents in Wenzhou were included as study subjects from April to May 2021. Data regarding the optical axial length, spherical equivalent refraction, number of children in a family, parental myopia, and close-work activities were collected through eye examinations and questionnaires. A multivariable logistic regression was used to analyze the association between the number of children in a family and optical axial length. Results The children were aged 9.80 ± 3.41 years. The overall percentage of children with an axial length > 24 mm was 38.9%, 44.5% in only children and 35.6% in multiples. The multivariable logistic regression analysis showed that the odds of having an AL > 24 mm were 1.24 times higher in only children than in multiples (OR: 1.24, 95% CI: 1.025-1.480, P = 0.028). Only children were 1.331 times more likely to perform homework > 1 h on weekends than multiples (OR: 1.331, 95% CI: 1.049-1.688, P = 0.019). Only children in upper grades were 1.543 times more likely to perform homework > 1 h on weekends than multiples (OR: 1.543, 95% CI: 1.065-2.235, P = 0.025). Boys who were only children were more likely to attend three or more extracurricular classes for academic subjects than multiples (OR: 1.224, 95% CI: 1.011-1.562, P = 0.004). Conclusions Being an only child may be associated with a higher risk of myopia and higher odds of close-work behaviors. Only children, especially those in upper grades, are more likely to spend more time on homework than their peers who are multiples. Only children, especially boys, are more likely to attend extracurricular classes in academic subjects. Trial registration This trial is registered as ChiCTR1900020584 at www.Chictr.org.cn .